A new classification and an extension of waste from business practices and Islamic perspective - Md Shahabuddin, Abu Saim; Abd. Sukor, Mohd Edil; Helal Uddin, A.B.M. (IIUM Press, International Islamic University Malaysia, 2019)
Abstract: Taking the idea of waste as an in-use phenomenon, we developed a matrix to explain four categories of waste which result from users’ failure to use a resource properly. These categories were illustrated by examples built on practical food waste measurements, surveys, theses formatting requirements and newspaper reports. We have categorized different facets of waste from a business perspective; thus, contributed to have improved waste management practices. We also showed that parsimony was also a wasteful behaviour. Parsimony was shown to be a waste by its effects on others’ need of fulfilment and other-worldly consequences for the miser.